Performance Analysis of the WDM Schemes for RoF System with Various Bit Rate - Febrizal Ujang; Affan Dahlan Siregar; Annisa Mardhotillah; Fildza Arifa; Natasya Yulia Ikhsan; Sonia Maharani Putri (Universitas Medan Area, 2023)
Communication that combines the methodologies of the two communications can be considered as communication fiber optic communication and can be used in communication systems and wireless. The integration of optical and wireless networks can function to increase mobility and capacity as well as reduce costs in access networks. Radio over fiber (RoF) can be a solution for many problems because it can control many base stations (BS) connected to a central station (CS) with an optical fiber. The high bit error rate (BER) and low Q factor value are caused by the Rof signal head received in low quality, so the receiver may not operate on high data speed networks. The solution to different signal problems and can be done with single mode fiber is the Wavelength Division Multiplexing (WDM) network. BER must be reduced to a guaranteed value, and the Q factor must be increased. WDM-RoF probes with different fiber lengths at various channel distances will be: simulated using Optisystem software, and the performance of the RoF receiver is measured and analyzed depending on the obtained BER, Q-factor value, and eye aperture height. The effects of degradation factors such as attenuation and dispersion are very limited with the addition of EDFA amplifier to Single Mode Fiber (SMF). The higher the bit rate of a communication system, the lower the performance of the system. In this study, analysis of the WDM-Rof system with bit rate variations was carried out to determine the bit rate value that still met the standard. From the simulation results, the Q-Factor and BER values at a bit rate of 11 Gbps do not meet the standards, i.e 4.50508 and 2.5390e-006.